Technology Diffusion or Capital Accumulation? An Empirical Assessment of Convergence in Manufacturing - Silvia Dal Bianco (Università degli Studi di Pavia, Dipartimento di Economia Politica e Metodi Quantitativi (EPMQ), 2010)
In this paper I consider 28 developed and developing countries, in the period 1980- 1995, and I employ the Within Group and the Generalized Method of Moments estimators to test, respectively, for Total Factor Productivity determinants and labor productivity convergence driving forces (i.e.capital accumulation and technological catch-up) in different manufacturing sectors, identified according the technological content of their production. Moreover, I test for inter-sectoral and cross-country heterogeneity of labor productivity convergence tendencies. My results show that technology growth rate is enhanced by technological transfer, in all manufacturing sectors and countries, and that cross-country convergence is determined by technology diffusion rather than capital accumulation. Further, I find that the rate of technological convergence appears higher in emerging economies, particularly in High Tech sectors. Finally, tertiary education seems to be relatively more important, as absorptive capability, than secondary one.
Keywords: O14; O47; L60; 330; Classical and Technological Convergence; Absorption Capabilities; Technological Gap; TFP growth; Manufacturing sectors; Panel data